PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN LANGKAH-LANGKAH POLYA PADA KELAS IV SD NEGERI 020/XI KOTO LEBU KOTASUNGAI PENUH KERINCI - Andam Yulianti; Riska -; Siska - (Jurnal Tunas Pendidikan, 2018)
Inthis study, the authors apply thelearning Polya steps to improve student learning outcomes. This study aimed to describe the planning, execution, and improved learning outcomes. This research was class room action research. Using qualitative and quantitative approaches.Subjects were teachers and students of class IV elementary School District 020/XI Koto Lebu Kota Sungai Penuh Kerinci. In thefirst cycleof teachersin designing learning skills 69.5%, 69.5% showed teacher activity and student activity 62.5%. Meanwhile, thesecondcycleis seen to rise. The abilityof teachersin designing learning to 86%. Activity to 87.5% of teachers, student activity to 83.5%. In short, action researchusing Polya steps to improve student learning outcomes